Isolated bilateral facial palsy due to chicken pox- An unique presentation - Nandini Chatterjee; Chandan Chatterjee (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
A nineteen year old girl presented with rashes of chicken pox and inability to close both eyes properly for two days. She had difficulty in eating and smiling. Vesicular non pruritic rashes were visible in various stages of healing over face and body except palm and soles. She complained of bilateral headaches but no vomiting, or weakness in her limbs or alteration of her taste sensation. She was alert and cooperative with normal speech and memory. B/L lower motor neuron type of facial nerve palsy was found. Routine blood work up, serology for HIV and Lyme disease, chest x ray, CSF study and MRI brain were normal. She was prescribed 60 mg of prednisolone and 4000 mg of acyclovir every day for 14days. She recovered completely from the neurodeficit within 14 days.